PENGARUH HARGA DAN KEMUDAHAN PENGGUNAAN APLIKASI SHOPEE TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Irma Aristia; Sugiono Sugiono; Rinnanik Rinnanik; Hikmatul Aliyah (Fakultas Ekonomi dan Bisnis, 2023)
The number of e-commerce in the digital era makes it easy for someone to make shopping transactions. E-commerce in Indonesia includes tokopedia bukalapak, shopee, lazada and blibli. Among young people, shopee is a very popular e-commerce for shopping transactions. The number of offers provided by the platform provides its own charm. With an attractive offer, this study aims, (1) Testing the effect of price on online purchasing decisions, (2) Testing the effect of ease of use of the shopee application on online purchasing decisions, (3) Testing the effect of price and ease of use of the shopee application on online purchasing decisions. The data collection techniques in this study were questionnaire, interview and documentation techniques. The population is all students of the faculty of economics and business at Bakti Nusantara Institute who have made purchase transactions at least 1 (one) time through the shopee application. The sample was taken with non probability sampling technique. This study uses multiple linear regression analysis, with the regression equation: Y = α + β1X1 + β2X2 + ℇ after the data is analysed, the regression equation is obtained as follows: Y = 4.660 + (-0.049X1 + 0.880X2). The sample in this study were 100 respondents from 468 students. The results of the study showed that the variables of Price and Ease of Use simultaneously had a positive and significant effect on Purchasing Decisions in students of the faculty of economics and business at Bakti Nusantara Institute, in the calculation of Fcount of 53.022 while Ftable is 3.07 and significant 0.000 <0.05. The R2 test results show that R Square 0.522 means that the purchase decision is obtained and explained by the price and ease of use variables.